Uncrowned kings: rituals and ritual objects in eighteenth–nineteenth century Portuguese royal acclamation ceremonies. Issue 1 (2nd January 2021) - Silva, Isabel Corrêa da; Seixas, Miguel Metelo de
ABSTRACT: This article examines the royal acclamation ceremonies of the Portuguese crown in order to grasp the responsiveness of the institution of the monarchy and regime to the challenges of modernity throughout the delicate watershed period of the late eighteenth and nineteenth centuries. The Portuguese Catholic and absolutist monarchy of the ancien régime had a strict protocol and a set of insignia of power that acted together at the moment of the acclamation and legitimation of each new king. The purpose of this research is to assess the adaptation and reinvention of these insignia and rituals according to the revolutionary demands of social change and secularization brought about by the turbulent period of the beginning of the nineteenth century: the French military invasions (1807–11); the departure of the royal family, court and administration to Brazil (1807); the liberal constitutional revolution (1820); and the civil war pitting liberals against absolutists (1832–34). The new constitutional monarchy that came out of this revolutionary flow faced many challenges of legitimacy, including the test of its capacity to create a modern royal imaginary updated to the cultural mindset of national and secular societies, and capable of bonding rulers with their people. The authors believe that the study of the acclamation ceremonies in the Portuguese constitutional monarchy can give us an accurate perspective on the quality of the symbolic image of the crown, therefore assessing the political efficiency of rituals as one of the structural aspects for institutional legitimization.